Imbalances of chromosome 17 in medulloblastomas determined by comparative genomic hybridisation and fluorescence in situ hybridisation. Issue 6 (1st December 2000) - Nicholson, J; Wickramasinghe, C; Ross, F; Crolla, J; Ellison, D
Abstract : Aims —To investigate the status of chromosome 17 in a series of medulloblastomas using comparative genomic hybridisation (CGH) and fluorescence in situ hybridisation (FISH). Methods —Frozen tissue and formalin fixed, paraffin wax embedded tissue from 27 medulloblastomas were analysed by CGH and FISH, respectively. CGH ratio profiles for chromosome 17 were compared with the results of FISH, for which loss or gain of 17p or 17q was assessed in two distinct ways using a combination of differentially labelled subtelomeric and centromeric probes and analysing 200 nuclei in each tumour. Results —CGH revealed imbalances consistent with isochromosome 17q in eight of 27 tumours. Either loss of 17p or gain of 17q was identified in a further nine tumours, whereas 10 tumours were apparently balanced. Using control results from preparations of paraffin wax embedded tonsils, thresholds for the detection of abnormalities by FISH were established, either by determining the dominant pattern of signals in each case, or the mean ratio of subtelomeric to centromeric signals. Results by CGH and FISH were concordant in 21 of 27 tumours. In the remainder, most discrepancies related to methodological differences. Conclusions —CGH has a role in disclosing common, genome wide chromosomal gains or losses in tumours, the clinical relevance of which can then be studied in large archival series of paraffin wax embedded tumours using FISH.